Analisis Nilai Tambah dan Strategi Pengembangan Agroindustri Siwalan di Desa Hendrosari, Kecamatan Menganti, Kabupaten Gresik - Devita Inka Amalia; Sri Widayanti; Dita Atasa (Universitas Batanghari Jambi, 2023)
The purpose of this study was to analyze the added value of siwalan dawet and legen siwalan products in Hendrosari Village, Menganti District, Gresik Regency and to analyze the strategy of developing Siwalan agroindustry in Hendrosari Village, Menganti District, Gresik Regency. The data analysis method used in this study was descriptive quantitative, covering the data processing stage and descriptive data interpretation. The analysis used consisted of value added analysis of the hayami method and SWOT analysis. The results obtained from this study are the added value resulting from processing siwalan fruit into siwalan dawet is higher than the added value from processing siwalan sap into siwalan legen. %, while the added value from processing siwalan sap into siwalan legen is IDR 1,000/bottle or 29%. The SWOT analysis shows the IFAS value of 3.05 and the EFAS value of 2.78. This value is in quadrant IV (stability growth), in the internal external matrix including the White Area, so the strategy that can be done is the S-O strategy. The S-O strategy is a strategy used to maximize the strengths and opportunities of the Siwalan agroindustry. The strategy that can be used is to strengthen relations with suppliers to maintain the availability of raw materials, maintain the existing market and expand the reach of market share, increase the production capacity of dawet siwalan.